The Effect of In–vitro Antibacterial Activity of Moringa & Tulsi Leaves Extract against Endometritic Repeat Breeding Cross Bred Cow - Kumar, S.; Sinha, M. P.; Barman, R. S. D.; Verma, R. K. (International Journal of Livestock Research, 2019)
The present study was conducted to see the effect of in–vitro antibacterial activity of Moringa & Tulsi leaves extract against endometritic repeat breeding cross bred cow at Military dairy farm, Namkum and local farmers in and around Ranchi, under supervision of Department of Veterinary Gynaecology and Obstetrics, Ranchi Veterinary College, Birsa Agricultural University, Kanke, Ranchi (Jharkhand),India. In the present study, the therapeutic efficacy of Moringa and Tulsi were assessed against endometritic repeat breeding crossbred cows. The endometritic repeat breeding animals were randomly allotted to five groups namely Groups A, B, C, D and E. Each group contained six animals. Extracts of Moringa and Tulsi were tested for In-vitro antibacterial activity against bacterial population in cervical mucus of repeat breeding crossbred cows. Estrual cervical mucus samples were collected before treatment (day of estrum) and tested for pH, white side test and bacterial load and again collected at subsequent estrus after treatment and the above-mentioned parameters were studied. Higher bacterial load was recorded prior to treatment which ranged from 212.83 to 256.33 3.07 x 106/ml in cervical mucus of endometritic repeat breeding cows. After treatment the mean bacterial load in group A, B, C, D and E recorded were 243.5 respectively. A marked & significant decline (p≤ 0.05) in bacterial load was recorded in all the groups from pre-treatment to post treatment except control group A. Bacterial load was significantly lowest (p≤ 0.05) in groups B followed by, group E, D, C.